Sharia Insurance Disputes Through Sharia Arbitration: A Legal Discourse - Sawitri Yuli Hartati; Fauzan Azhim (Journal Equity of Law and Governance, 2024)
Sharia insurance in Indonesia has experienced significant growth, accompanied by increasingly complex disputes between Islamic insurance companies and policyholders. The primary issue lies in the fragmented legal framework for resolving sharia insurance disputes, with relevant provisions spread across multiple laws and regulations. This has become a discourse and issue of legal norms for sharia arbitration as an option for Islamic arbitration is currently governed by Supreme Court Regulation Number 14 of 2016 and governs the settlement of sharia insurance claims. The research method used is descriptive normative by analyzing regulations laws governing sharia dispute resolution. The results of this study explain that state policy in managing sharia Article 58 of Law No. 48 of 2009 concerning Judicial Power is still used by constitutional authority because insurance issues are still being discussed. Law No. 30 of 1999 must therefore be amended, particularly the section pertaining to the District Court, which needs to be enhanced by the Religious Courts and the processes for settling conflicts through sharia arbitration.